New Star Football Academy Fitness Players Aged 3 and 14 Years - Muftah Mohamed S. Belhaj; Soegiyanto Soegiyanto; Hari Setijono; Hari Pramono; Sulaiman Sulaiman; Didi Yudha Pranata (International Conference on Science, Education, and Technology, 2023)
This study aims to determine the fitness level of new star academy football players. The research method uses quantitative. The research subjects were New Star Football Academy players aged 13-14 years, totaling 26 players. The instrument used in this study was the 2.4 KM run test from Cooper. Descriptive percentage as an analytical technique used in this study. The results of the research yielded very good category information 8%, good 27%, moderate 46%, less 15% and very less 4%. The coach's advice is to pay attention to the player's fitness level because fitness level is an important factor to maintain game performance on the field by providing fitness exercises such as fartlek training, high intensity interval training and training circuits taking into account the characteristics and age of the players.